Treatment modalities of oral lichen planus: an update - Patil, Santosh; Khandelwal, Suneet; Sinha, Nidhi; Kaswan, Sumita; Rahman, Farzan; Tipu, Shoaib (Journal of Oral Diagnosis, 2016)
Oral lichen planus is an immunologically based, chronic, inflammatory, mucocutaneous disorder of undetermined etiology. It is a relatively common disorder affecting stratified squamous epithelia. It is of special importance due to its malignant potential and can be a source of morbidity. The management of oral lichen planus should therefore address both the transformation rate as well as the patient symptoms. Care and management of such patients challenges even the most experienced clinician. There is currently no cure for OLP. Treatment is aimed primarily at reducing the length and severity of symptomatic outbreaks.The review critically analyses the various options in the literature and discusses the practical management from the Indian perspective.